In search of proximate enemies. Issue 4 (2nd October 2017) - Iwabuchi, Koichi
Abstract : Abstract: The post-Cold War context has accompanied the ascent of East Asian economies and consumer markets, as exemplified by China, while Japan's experience has been marked by the struggle with an economic slump after the collapse of the so-called bubble economy. Japan has been actively promoting 'cool Japan' instead of the economy, but even more notable is the rise of the Korean Wave. Joined together with political contestation over historical issues, anti-China/Korea sentiments have been growing, as is the accompanying hate-speech movement against resident Koreans in new-millennium Japan. Growing East Asian rivalry along with the relative decline of Japan, the widely shared sense of socio-economic predicament and the upsurge of digital media communications have been conjoined to generate the hunt for proximate enemies – China, Korea, and resident Koreans in Japan – as the object of expressions of hate. How to develop better uses of digital media towards the cultivation of dialogic cultural citizenship is an imperative issue.